Phenotypic Changes Associated With In Vivo Evolution of Colistin Resistance in ST11 Carbapenem-Resistant Klebsiella pneumoniae - Xie, Miaomiao; Chen, Kaichao; Dong, Ning; Xu, Qi; Chan, Edward Wai-Chi; Zhang, Rong; Chen, Sheng (Frontiers in Cellular and Infection Microbiology, 2022)
Colistin is one of the few antibiotics that exhibit bactericidal effect on carbapenemase-producing Klebsiella pneumoniae strains. In recent years, however, colistin resistance is increasingly being reported among clinical carbapenem-resistant K. pneumoniae strains worldwide, posing serious challenge to treatment of infection caused by these organisms. In this study, we investigated one colistin-susceptible (YJH4) and one colistin-resistant (YJH15) K. pneumoniae strain, which were collected from a patient before and after colistin treatment, respectively. We characterized the effects of mgrB inactivation-induced colistin resistance on the physiological fitness and virulence in ST11 carbapenem-resistant K. pneumoniae both in vitro and in vivo. The colistin-resistant strain YJH15 was found to exhibit increased fitness and biofilm formation potential in vitro, and increased survival rate in the presence of normal human serum. Interestingly, YJH15 exhibited reduced virulence in the mouse infection model but enhanced virulence in Galleria mellonella infection model when compared to the colistin-susceptible parental strain YJH4. Infection with YJH15 was also found to result in lower expression level of inflammatory cytokine IL-1β in blood and significantly decreased bacterial loads in heart, liver, spleen, lung, kidney and blood. These results demonstrated that mgrB inactivation-induced colistin resistance has significant effects on multiple fitness and virulence-associated traits in K. pneumoniae. These findings have important implications in fine-tuning antimicrobial stewardship programmes and patient management.